Sorption kinetics of an eco-friendly and sustainable Cr (VI) ion scavenger in a batch reactor - Singh V.; Singh J.; Mishra V. (My University, 2025)
In the present work, Cr (VI) was successfully biosorbed and reduced to less toxic Cr (III) by using chitosan coated MnO2 nanoparticles synthesized through green route using curcumin and Citrus limetta peel extract. X-ray photoelectron spectroscopic analysis of chromium loaded nanoparticles confirmed that most of the Cr (VI) ions were reduced to Cr (III). Scanning electron and transmission electron microscopic images showed that these nanoparticles were spherical in shape, crystalline in nature, ranged from 14 to 24 nm in size. The Fourier-Transform infrared spectroscopy analysis indicated hydroxyl, carboxyl and amino groups on its surface. The dynamic light scattering showed a size distribution of nanoparticles as 299.50 ± 25.32 nm. High Brunauer-Emmett-Teller specific surface area (76.19 m2/g) of these nanoparticles provided more active sites for binding of chromium ions. Energy dispersive X-ray and ultimate analysis indicated the presence of Mn, O, C, H, and N. These elements were the major components of these nanoparticles and confirmed the presence of chitosan on nanoparticle surface. The lower value of pHzpc (3.17) proved the suitability of acidic pH values for conducting biosorption experiments. The values of dimensionless numbers and diffusivity coefficients indicated that biosorption was controlled by film and pore diffusion. Pseudo-second order (R2 = 0.99) and Freundlich isotherm (R2 = 0.99) showed a better goodness of fit over other kinetic and isotherm models. The thermodynamic study showed that biosorption was exothermic and spontaneous. But, the enthalpy is endothermic and the reaction is entropy driven. Results showed that these nanoparticles have high Cr (VI) uptake capacity (92.19 mg/g) and can be reused over several cycles of adsorption-desorption. © 2021 Elsevier Ltd.